ARCHITECTURE AS A REALIZATION OF THE NEED OF THE RELIGIOUS CULTURE IN INDONESIA - Monitha, Cheria; Haryono, Traviata Nabiilah Widi; Susanti, Wiwik Dwi (Border: Jurnal Arsitektur, 2021)
Culture is an idea or a system of ideas that arise as a result of the social behavior of society. The existing system in culture includes norms, values, views of life, and one of them is belief. Belief itself is supported by the values and customs that are believed by certain communities and carried out from generation to generation. Gradually, the culture will form a pattern of needs, such as rituals and places of worship. It is known that, places of worship that already exist in Indonesia have different characteristics with the concept of belief in each region. These different and diverse characteristics are clear evidence of differences which are at the same time a cultural wealth for the face of the region itself. This makes architecture one of the concrete manifestations of culture and fulfillment of needs, this embodiment can reflect the identity of the area. From the analysis carried out, it can be concluded that architecture is a tangible form of the face of a culture, one of which is in terms of belief or religion and in the process of making this journal, this study uses data collection methods from various sources.